The Influence of Original Regional Income on Regional Expenditures in Regencies/Cities in West Java Province - Dede Riswandi (Jurnal Syntax Admiration, 2023)
The Purpose of the research is to know how much the influence of regional original revenue to regional expenditure on the local goverment city/regency in west java province. The research approach used in sample of this research is Budget Realization Report of Local Government in West Java Province. The method used in this research is descriptive and verifikatif method. Data collection techniques are conducted through secondary data, the data obtained from the Badan Pusat Statistik (BPS) in West Java Province.Statistical analysis used in this study is normality test, autocorrelation test, simple linear regression analysis, person correlation analysis, coefficient of determination analysis, and t hypothesis and assisted with data processing using SPSS 25.0 for Windows.The result of the research show that regional original revenue has an effect on regional expenditure on the local goverment city/regency in west java province. The influence of regional original revenue on regional expenditure means that the higher the regional original revenue, the more the regional expenditure will increase.